Художня деталь в архітектоніці роману Івана Білика "Дикі білі коні" - Хорольська, Тетяна; Khorolska, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто сюжетні лінії, особливості хронотопу, використання художньої деталі, її композиційну та характерологічну функції, символізм художніх деталей в історичному романі «Дикі білі коні» відомого українського письменника Івана Білика.This article examines the storylines, features of chronotope, using of artistic details, its composition and characterological features, the symbolism of artistic details in the historical novel “Wild white horses” of the famous Ukrainian writer Ivan Bilyk. The plot structure of the novel is quite simple. The author outputs two heroes-antipodes to the center of the story – the king of the Persians Dariavaush and Prince of Drevlyans Borymysl. The architectonic of this novel built around these characters. The rapid development of the plot, narrative dynamism, intensive dialogue, copyright digressions, monologues are typical for the novel “Wild white horses”. One event quickly replaced by another. There are noted that author most often uses one-time artistic detail in the novel, but there are also repeated item symbol, which requires the reader’s knowledge of Ukrainian customs, traditions, symbols, and characterizes Ivan Bilyk as a master of artistic expression in the article.
Artistic Detail in the Architectonics of Ivan Bilyk’s Novel “Wild White Horses”
Keywords: історичний роман; сюжет; художня деталь; хронотоп; символ; historical novel; plot; artistic detail; chronotop; symbol